DIFFERENTIAL VARIATIONAL INEQUALITIES VIA THE EXTENDED LASALLE’S INVARIANCE PRINCIPLE APPROACH - Mai Huong, Hoang; Thi Nhung, Nguyen (HNUE Journal of Science: Journal of Natural Sciences, 2025)
In this work, we establish an extended LaSalle’s invariance for a class of nonautonomous differential inclusions in Euclidean spaces. We also give sufficient conditions for the stability of an equilibrium of differential variational inequalities. Special cases as linear complementarity problems, based on LaSalle’s invariance in both autonomous and non-autonomous cases, are also studied in this paper.